An elastomeric seismic isolator. - Muhammad Rashid, Raizal Salfulnaz (2012)
An elastomeric seismic isolator comprising: stacked high damping rubbers sandwiched by two steel plates forming a unit cell characterized in that the stacked high damping rubbers are alternately arranged and adhered with carbon fiber reinforced polymer plates. The above provision is advantageous as weight reduction of the isolator is possible since the carbon fiber reinforced polymer behaves identically with steel plates in terms of the elastic stiffness. Therefore, the reinforcement needed to provide the vertical stiffness be obtained by using the similar volume of very much lighter material.